Exercícios para melhoria da capacidade funcional: uma estratégia virtual de promoção da saúde em pacientes em hemodiálise - Galhardi, Caroline Hidalgo (2022)
Introduction: Chronic kidney disease and hemodialysis can lead to decreased strength and loss of muscle mass, resulting in a progressive loss of physical capacity and directly influencing the quality of life of patients. Physical exercise is capable of restoring, developing and conserving physical capacity, promoting muscle strengthening and gain in range of motion, contributing to an improvement in quality of life. Objectives: To evaluate the effects of a virtual physical exercise program on the physical and functional capacity of hemodialysis patients. Methods: This is a longitudinal, quantitative research with hemodialysis patients at the Nephrology Service in the city of Matão-SP. Data collection took place during two months with evaluations before, during and post-intervention. Patients received the exercises through video demonstration classes available on virtual platforms. Results: Thirty-one patients participated in the study, 8 women and 23 men, with a minimum age of 28 and a maximum of 74 years. Most patients were overweight at baseline and there was no change in body weight after the intervention. It was observed that the older the patients, the longer they took to perform the time up and go test (p=0.013); this test, when correlated with the sarcopenia questionnaire, indicated that the longer the time to perform it, the higher the sarcopenia index (p=